Orthodoxy and enlightenment : George Campbell in the eighteenth century - Suderman, Jeffrey M. (Jeffrey Mark), 1965- (McGill-Queen's studies in the history of ideas ;, 2001)
Employing an interdisciplinary approach that gives equal consideration to Campbell's secular and religious writings, Jeffrey Suderman argues that Campbell used the critical tools of the Enlightenment to defend an orthodox Christian faith. This conclusion will oblige both historians and critics of the Enlightenment to reassess long-held assumptions about the secular nature of eighteenth-century thought and culture.